Continuousness of interactions between hydrogen and plastic deformation of ultra-high strength steel sheet consisting of ferrite and nanometer-sized precipitates. (3rd October 2022) - Takashima, Katsutoshi; Han, Ruoyu; Yokoyama, Ken'ichi; Funakawa, Yoshimasa
ABSTRACT: The continuousness of the interactions between hydrogen and plastic deformation of an ultra-high strength steel sheet consisting of ferrite and nanometer-sized precipitates has been investigated by tensile tests after or during cathodic hydrogen charging. In the tensile test in the air after hydrogen pre-charging, a hydrogen thermal desorption analysis shows that the amount of hydrogen desorbed decreases with increasing applied tensile strain from room temperature to 50 °C, but increases in the high temperature region. Upon tensile straining to 0.06, no hydrogen is desorbed in the low temperature region, and the change in desorption behaviour when strain exceeds 0.06 is negligible. This suggests that substantial interactions between hydrogen and plastic deformation in the test with hydrogen pre-charging occur only in the early stages of deformation. In contrast, in the tensile test during hydrogen charging, the hydrogen desorption which begins from room temperature continues even upon tensile straining to 0.06, suggesting continuous interactions, and a unique dislocation structure resembling sub-grain boundaries is observed. Upon aging at room temperature after tensile straining to 0.06 during hydrogen charging, all hydrogen desorption lower than 100 °C shifts to the high temperature region, but the recovery of elongation is not necessarily complete. When tensile strain is applied during hydrogen charging, continuous interactions presumably induce anomalous damage, thereby enhancing the degradation of ductility. The results of the present study strongly support the conclusion that the continuousness of the dynamic interactions between hydrogen and plastic deformation plays essential roles in hydrogen embrittlement of ferritic steel.